Corrosion fatigue of engineering alloys in aqueous environments - Harty, Brian Dudley (Centre for Materials Engineering, 2016)
A comparative study of the fatigue crack growth rate (FCGR) behaviour of five alloys in air and in aqueous environments has been performed. The alloys tested include: mild steel as a reference material, a corrosion resistant dual phase steel, 3CR12, a proprietary martensitic stainless steel, AISI 431, a newly developed 8% Cr martensitic steel, Alloy 825, and a newly developed corrosion-abrasion resistant metastable austenitic alloy, 1210. Tests were conducted in laboratory air, distilled water at rest potential, 500 ppm chloride solution at rest potential, 1000 ppm chloride solution at rest potential, and 1000 ppm chloride solution at -1200 m V see; solution temperatures were maintained at 25⁰ C. Crack growth rate tests were performed using sinusoidal loading at a load ratio R = 0.1, a frequency of 3Hz in the laboratory air, and a frequency of 1 Hz in the aqueous environments. At the completion of testing, fracture surfaces were studied using a scanning electron microscope. In air, the mild steel and 3CR12 display comparable rates of cracking and exhibit a greater resistance to fatigue crack propagation than the martensitic AISI 431 and Alloy 825; Alloy 825 shows the least resistance to fatigue crack propagation. The deformation induced transformation in 1210 gives this alloy the greatest resistance to fatigue crack propagation in air. Fatigue crack growth rates were all enhanced in the aqueous environments. The greatest overall rate of environmentally assisted cracking was shown by alloy 825 while the lowest was shown by the mild steel. Although the rate of cracking of 1210 in the aqueous environments was less than that of Alloy 825, 1210 was influenced the most by the aqueous environments. An environmentally assisted cracking index shows that the rate of fatigue crack propagation in 1210 is increased by 32 times in the 500 ppm chloride solution at low stress intensities. The fatigue crack growth rates of mild steel and AISI 431 were significantly influenced by the cathodically polarised conditions in the 1000 ppm chloride solution, compared to the rest potential conditions. In these cases hydrogen was seen to be evolved from the specimen surfaces. Changes in the fatigue crack growth rate behaviour were accompanied by changes in the fracture surface morphologies. The observed changes varied for each alloy and for each environment, and were manifest by the degree of intergranular cracking, cleavage, quasi cleavage, and increased coarseness of the transgranular cracking. The fracture surface morphologies are reported and discussed in detail. In general, the fracture surface morphologies could be directly related to the relative degrees of environmental influence on the rate of cracking; results are explained in terms of existing hypotheses. It is suggested that the environmentally assisted cracking of mild steel and AISI 431 at cathodic potentials in the 1000 ppm chloride solution could only be attributed to hydrogen assisted cracking. Similarly, it is suggested that the large crack growth rate acceleration of 1210 in the aqueous environments could also be attributed to hydrogen. The similar fracture surface morphologies observed on the other specimens after tests in the aqueous environments suggests-that hydrogen could be responsible for the environmentally assisted cracking of all the steels in aqueous environments.